Путешественники конца XVIII – первой половины XIX века о памятниках древности Керчи (храм Св. Иоанна Предтечи) - Авсенёва, С.Н. (Культура народов Причерноморья, 2014)
Статья представляет результаты анализа текстов зарубежных (английский текст работы путешественника Г. Сеймура представлен в авторском переводе) и отечественных путешественников по Крыму конца XVIII – первой половины XIX в. Работа, проделанная со свидетельствами, оставленными в путевых дневниках, о тогдашнем состоянии храма современной православной церкви Святого Иоанна Предтечи в Керчи, позволила определить высокую ценность записок путешественников как исторического источника по истории Крыма. Стаття представляє результати аналізу текстів зарубіжних (англійський текст роботи мандрівника Г. Сеймура представлений в авторському перекладі) та вітчизняних мандрівників по Криму кінця XVIII – першої половини XIX в. Робота, виконана зі свідченнями, залишеними в мандрiвних щоденниках, про тогочасний стан храму сучасної православної церкви Святого Іоана Предтечі в Керчі, дозволила визначити високу цінність записок мандрівників як історичного джерела з історії Криму. This article presents the results of the text’s analysis of foreign (primarily the English text of the traveler G. Seymour presented in the author's translation) and domestic travelers to the Crimea in the late 18th to the first half of the 19th centuries. Interest in this topic of research is due to the particular value placed on such an historical source for the history of Russia from the perspective of the traveler. However, despite this intrinsic value, very little scrutiny by researchers has been conducted on works up to the beginning of the 19th century. To some extent, this is due to the complexity of the research required to discover the various travel notes as well as the nature of the material in and of itself. This is especially true for the works of foreign travelers. Researchers often paid attention to the works of only certain travelers; preference having been given to what they believed to be the most meaningful texts. Proceedings of many travelers still remain unexplored or even unknown. The necessity to discover, analyze, and study all available travelers’ works of this period explains the intent of the present research. The work being accomplished with the information within the various travel diaries relating to the state of the temple of modern Orthodox Church of St. John the Baptist in Kerch as it was, has allowed us to recognize the high value of travelers' notes as an historical source for the history of the Crimea.